Aromaterapi Jahe terhadap Skala Mual Pasca Kemoterapi Pasien Kanker - Nurul Khafifah; Wa Ode Sri Asnaniar; Munir , Nur Wahyuni; Safruddin (Window of Nursing Journal, 2024)
Chemotherapy is a pharmacological therapy that can be given to cancer patients. Giving chemotherapy to patients can cause effects, one of which is nausea and vomiting, but this effect can be alleviated by giving non-pharmacological therapy using ginger aromatherapy therapy. This study aims to determine whether there is a ginger aromatherapy agent on reducing nausea after chemotherapy for cancer patients in the Mawar Room, Pelamonia Hospital Tk.II Makassar. The design of this study used a pre-experimental research with a one group pretest-posttest design with purposive random sampling and a sample size of 32 respondents. Bivariate test using Wilcoxon test (α = < 0.05). The results of the study from 32 respondents obtained a bad category on the nausea scale as much as 71.9% and a good category as much as 28.1% before being given ginger aromatherapy then it became 100% with a good category after being given ginger aromatherapy therapy with a p value of 0.001. The conclusion of this study shows that ginger aromatherapy is beneficial for cancer patients after chemotherapy to reduce the scale of nausea and vomiting. It is hoped that nurses can apply complementary therapies to patients for nursing care and can help further researchers as references in their research